2013
DOI: 10.1080/10255842.2012.664637
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative underwater 3D motion analysis using submerged video cameras: accuracy analysis and trajectory reconstruction

Abstract: In this study we aim at investigating the applicability of underwater 3D motion capture based on submerged video cameras in terms of 3D accuracy analysis and trajectory reconstruction. Static points with classical direct linear transform (DLT) solution, a moving wand with bundle adjustment and a moving 2D plate with Zhang's method were considered for camera calibration. As an example of the final application, we reconstructed the hand motion trajectories in different swimming styles and qualitatively compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 21 publications
(34 reference statements)
1
30
1
1
Order By: Relevance
“…Ceccon et al (2013) found a coefficient of variation of 7.58% for a 10 cm reference wand moving through the calibrated, underwater volume. Silvatti et al (2013) compared different calibration procedures and found a coefficient of variation as low as 0.24% for a 3 m wand, which is much larger than the rigid body used in our study to calculate dynamic precision. In contrast to the aforementioned studies in which a wand was moved through the calibrated volume, we studied the precision during the underwater phase of the stroke.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Ceccon et al (2013) found a coefficient of variation of 7.58% for a 10 cm reference wand moving through the calibrated, underwater volume. Silvatti et al (2013) compared different calibration procedures and found a coefficient of variation as low as 0.24% for a 3 m wand, which is much larger than the rigid body used in our study to calculate dynamic precision. In contrast to the aforementioned studies in which a wand was moved through the calibrated volume, we studied the precision during the underwater phase of the stroke.…”
Section: Discussionmentioning
confidence: 87%
“…The movement of the body parts through the water generates extra bubbles, which most likely increases reconstruction errors due to additional refraction. In addition, different calibration procedures (Silvatti et al, 2013), camera positions and camera resolutions could have caused differences in precision between studies. As pointed out by Figueiredo et al (2011), the precision obtained in motion analysis systems for swimming is influenced by image distortion and by errors related to digitisation and 3D reconstruction (Payton and Bartlett, 1995;Kwon and Casebolt, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the uncertainty of measurement is 0.033 s, which is the duration of one frame. Furthermore, the hypothesis of a symmetric arm coordination, made here, is not completely exact, because an asymmetry linked to the swimmer's technique (Silvatti et al, 2013;Tourny-Chollet, Seifert, & Chollet, 2009) or to the breathing (Seifert, 2010;Seifert, Chollet, & Allard, 2005) can exist.…”
Section: Discussionmentioning
confidence: 93%
“…Others have provided an extensive examination of the technical aspects of underwater videography, with an emphasis on calibration and reconstruction procedures. [21][22][23] No review has been published specifically assessing the processes by which video is captured in applied swimming settings. This may result in uncertainty amongst coaches and practioners regarding the most appropriate methodologies to be adopted and the value of video in swimming.…”
mentioning
confidence: 99%